Professional internships and the skills of the administrator: a study with graduates and graduates of a federal Higher Education Institution (Research, Society and Development, 2020)
The present work has the objective of discussing the contributions of the professional internships to the development of competencies of the administrator, graduated in a federal HEI. The methodology used is qualitative, consisting of a survey study with students and graduates of the Administration course. Data were collected through a questionnaire sent by e-mail, containing four questions about experiences during the undergraduate internship. As a result, the study presents the reasons for the internship search, the related and non-course activities developed by trainees, the aspects that facilitate or hinder the insertion of the student in the job market, besides the skills and abilities developed during the internship. Finally, the study points out that the internship contributes mainly to the development of managerial behavioral skills, among them communication and proactivity, and little development of technical skills.